Politik Anggaran Pinjaman Daerah dalam Pembiayaan Pembangunan di Kabupaten Manggarai Tahun 2021-2023 - Syafruddin, Akhmad; Nami, Yohanes Jimmy; Luju, Kornelia (Brawijaya University, 2024)
Regional Loans are an alternative funding instrument used by the Manggarai Regency government, East Nusa Tenggara (NTT) Province, to finance regional development. Political support and the interests of political parties can influence the negotiation process in obtaining legislative approval. This research aims to determine how regional loans work and analyse the relationship between the executive and legislature in the political discussion and approval process in formulating regional loans. This research uses a qualitative approach and qualitative descriptive method, collecting information through primary and secondary data and determining informants using purposive techniques. The research results show that there are strong political dynamics, and there are differences in the interests of the views of each faction in discussions at the DPRD plenary meeting. The strength of the factions supporting the government dominates the discussions, further strengthening the regent's proposal for regional loans. The power of the executive and the majority of factions supporting the government are a strong driving force in smoothing the success of regional loans in Manggarai Regency. The faction that does not approve can finally accept and approve the loan, noting that regional loans must benefit the interests of development and community welfare.